The Development of Sports in the Healthy Upbringing of the Younger Generation (Eurasian Journal of Humanities and Social Sciences, 2023)
This article provides information on the legal framework for the development of sports in the Republic of Uzbekistan and reforms in the field of physical culture and sports in our country